2022
DOI: 10.3390/ma15134397
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Microstructure of Alkali-Activated Rice Husk Ash-Granulated Blast Furnace Slag Tailing Composite Cemented Paste Backfill

Abstract: At present, the research on rice hull ash and cement-based materials as cementitious materials continues to deepen. Low-cost rice hull ash replaces part of Portland cement, which plays a dual role in saving material costs and improving environmental benefits. In this study, alkali-activated rice husk ash (RHA) and ground granulated blast furnace slag (GGBS) were used to prepare cementitious material. The influence of RHA dosage on the strength, slump degree, and coagulation time of cementitious material was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The gelling materials used in this experiment were RHA and slag, the aggregate was tailing sand, and the exciter solution materials were NaOH, water glass and water. The RHA accounted for 10% of the cementing material, the fixed slurry concentration was 83%, the alkali-activated modulus was 1.0, the amount of alkali used was 4% of the mass of the cementing material, and the water-cement ratio was 0.35 32 . The above materials and proportions were used to make the surrounding rock slurry and filling slurry, and the slurry was poured into the Φ 50 mm × L 100 mm mold that had been well oiled.…”
Section: Methodsmentioning
confidence: 99%
“…The gelling materials used in this experiment were RHA and slag, the aggregate was tailing sand, and the exciter solution materials were NaOH, water glass and water. The RHA accounted for 10% of the cementing material, the fixed slurry concentration was 83%, the alkali-activated modulus was 1.0, the amount of alkali used was 4% of the mass of the cementing material, and the water-cement ratio was 0.35 32 . The above materials and proportions were used to make the surrounding rock slurry and filling slurry, and the slurry was poured into the Φ 50 mm × L 100 mm mold that had been well oiled.…”
Section: Methodsmentioning
confidence: 99%
“…As a safe and environmentally friendly disposal method for tailings, backfilling has significant advantages in controlling surface deformation and in improving ore recovery. Its benefits for use in underground mines are being recognized increasingly around the world [1][2][3][4][5][6][7]. The materials comprising cemented paste backfill (CPB) are important in maintaining mine safety and stability [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [27] found that applying fly ash to backfill materials can reduce drying shrinkage. Zhao et al [28] used activated rice husk ash and ground granulated blast furnace slag to prepare cementitious materials for cement slurry backfill and found that 10% rice husk ash can achieve higher strength. Yue [29] and Zhang et al [30] found that waste glass can replace some cement or be used as a binder for CTB with low-purity metakaolin, which can reduce backfilling costs.…”
Section: Introductionmentioning
confidence: 99%